2014
DOI: 10.1111/chd.12199
|View full text |Cite
|
Sign up to set email alerts
|

An Increased Incidence of Total Anomalous Pulmonary Venous Connection among Hispanics in Southern Nevada

Abstract: We found a significantly higher incidence of isolated total anomalous pulmonary venous connection in Hispanics vs. non-Hispanics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…There was no statically significant difference in the overall prevalence of CCHD for Hispanics versus non-Hispanics other than isolated total anomalous pulmonary venous return (TAPVR). Similar to our previous publication, 13 the prevalence of isolated TAPVR was 0.24/1,000 live births in Hispanics versus 0.05/1,000 live birth prevalence in non-Hispanics ( P = .01).…”
Section: Resultssupporting
confidence: 89%
“…There was no statically significant difference in the overall prevalence of CCHD for Hispanics versus non-Hispanics other than isolated total anomalous pulmonary venous return (TAPVR). Similar to our previous publication, 13 the prevalence of isolated TAPVR was 0.24/1,000 live births in Hispanics versus 0.05/1,000 live birth prevalence in non-Hispanics ( P = .01).…”
Section: Resultssupporting
confidence: 89%
“…1,2 Patients with scimitar syndrome and multiple congenital anomalies can be challenging to manage due to their multiple organ system pathologies.Although some forms of CHD have been linked to various genetic syndromes, the mechanisms that contribute to scimitar syndrome remains elusive. [3][4][5][6][7][8][9] Studies have demonstrated an association between scimitar syndrome and extracardiac anomalies including congenital diaphragmatic hernia, imperforate anus, and variants of VACTERL association. [10][11][12][13][14] Although pathogenic variants in specific genes can clearly cause CHDs, the genetic factors contributing to most cases of scimitar syndrome remain unidentified.…”
mentioning
confidence: 99%
“…[10][11][12][13][14] Although pathogenic variants in specific genes can clearly cause CHDs, the genetic factors contributing to most cases of scimitar syndrome remain unidentified. [3][4][5][6][7][8][9] In this study, we sought to determine the frequency and efficacy of genetic testing in patients with scimitar syndrome from a single institution. We also use the results of clinically based genetic testing to identify genes and pathways whose alteration may lead to scimitar syndrome development.…”
mentioning
confidence: 99%
“…The most frequent type of CHD described in the literature is ventricular septal defects (Table 1). However, TACVP is one of the most common complex forms of CHD in the Mexican population (Evans et al, 2015); therefore, we cannot rule out a potential predisposition to this type of CHD due to the patient's ethnicity. We propose that patients with these clinical characteristics, including TACVP, and family history consistent with an X-linked inheritance pattern, should be evaluated for GBBB.…”
Section: Discussionmentioning
confidence: 94%